Systematic Bibliometric Review on Sustainable Development in Islamic Perspectives 2005–2024 - Judijanto, Loso (West Science Islamic Studies, 2026)
This study presents a systematic bibliometric review of scholarly research on sustainable development from Islamic perspectives published between 2005 and 2024. Using bibliometric techniques and science mapping approaches, the study analyzes publication trends, thematic evolution, collaboration patterns, and the intellectual structure of the field. The findings reveal a steady growth of publications, with sustainable development occupying a central conceptual position closely linked to Islamic finance, banking, and economic growth. Over time, the literature has shifted from fragmented structural and sectoral discussions toward more integrated and impact-oriented themes, particularly Islamic social finance instruments such as zakat, waqf, and Islamic microfinance, alongside emerging concerns related to fintech, poverty alleviation, climate change, and Islamic education. Collaboration analyses indicate that research production is regionally concentrated, with Southeast Asia (especially Malaysia and Indonesia) serving as the primary global hub, while cross-regional collaboration remains uneven. The study highlights both the growing maturity and existing gaps in the field, underscoring the need for greater thematic diversification, interdisciplinary integration, and broader international collaboration to advance Islamic contributions to global sustainable development discourse.